Unsteady numerical simulation of a round jet with impinging microjets for noise suppression - Lew, Phoi-Tack (Acoustical Society of America, 2013)
The objective of this study was to determine the feasibility of a lattice-Boltzmann method (LBM)-Large Eddy Simulation methodology for the prediction of sound radiation from a round jet-microjet combination. The distinct advantage of LBM over traditional computational fluid dynamics methods is its ease of handling problems with complex geometries. Numerical simulations of an isothermal Mach 0.5, Re(D) = 1 × 10(5) circular jet (D(j) = 0.0508 m) with and without the presence of 18 microjets (D(mj) = 1 mm) were performed. The presence of microjets resulted in a decrease in the axial turbulence intensity and turbulent kinetic energy. The associated decrease in radiated sound pressure level was around 1 dB. The far-field sound was computed using the porous Ffowcs Williams-Hawkings surface integral acoustic method. The trend obtained is in qualitative agreement with experimental observations. The results of this study support the accuracy of LBM based numerical simulations for predictions of the effects of noise suppression devices on the radiated sound power.